Proceedings of the 2nd  International Seminar on Guidance and Counseling 2019 (ISGC 2019) 2020
DOI: 10.2991/assehr.k.200814.031
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Sites Usage and Fear of Missing Out among Female Instagram User

Abstract: The aim of this investigation was to examine the correlation between social network sites usage and fear of missing out (FOMO) of female instagram user with age ranged from 18 to 27. The responden involved 106 female college student of female instagram user from various university in west, east, and central java, Indonesia. The data collected randomly through an online link Google Form use 2 psychological scale, Student Form Social Media Addiction Scale (SMAS-SF) developed by Sahin and Fear of Missing Out Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The one-study-removed technique revealed that none of the included studies influenced or skewed the final results. However, among 85 articles (86 effect-sizes) included in the analysis, 21 articles had a moderate risk of bias ( Alt & Boniel-Nissim, 2018a , 2018b ; Barber & Santuzzi, 2017 ; Barry & Wong, 2020 ; Burnell, George, Vollet, Ehrenreich, & Underwood, 2019 ; Buyukbayraktar, 2020 ; Classen, Wood, & Davies, 2020 ; Elhai et al, 2016 ; Fuster, Chamarro, & Oberst, 2017 ; Hishan, Ramakrishnan, & Qureshi, 2020 ; McAndrew, 2018 ; Metin-Orta, 2020 ; Munawaroh, Nurmalasari, & Sofyan, 2020 ; O’Connell, 2020 ; Rahardjo & Mulyani, 2020 ; Riordan et al, 2020 ; Rogers & Barber, 2019 ; Schneider & Hitzfeld, 2019 ; Sha, Sariyska, Riedl, Lachmann, & Montag, 2019 ; Sheldon, Antony, & Sykes, 2021 ; Tang, Hung, Au-Yeung, & Yuen, 2020 ; Tunc-Aksan & Akbay, 2019 ) and the rest had a high quality and low risk of bias judged by the authors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The one-study-removed technique revealed that none of the included studies influenced or skewed the final results. However, among 85 articles (86 effect-sizes) included in the analysis, 21 articles had a moderate risk of bias ( Alt & Boniel-Nissim, 2018a , 2018b ; Barber & Santuzzi, 2017 ; Barry & Wong, 2020 ; Burnell, George, Vollet, Ehrenreich, & Underwood, 2019 ; Buyukbayraktar, 2020 ; Classen, Wood, & Davies, 2020 ; Elhai et al, 2016 ; Fuster, Chamarro, & Oberst, 2017 ; Hishan, Ramakrishnan, & Qureshi, 2020 ; McAndrew, 2018 ; Metin-Orta, 2020 ; Munawaroh, Nurmalasari, & Sofyan, 2020 ; O’Connell, 2020 ; Rahardjo & Mulyani, 2020 ; Riordan et al, 2020 ; Rogers & Barber, 2019 ; Schneider & Hitzfeld, 2019 ; Sha, Sariyska, Riedl, Lachmann, & Montag, 2019 ; Sheldon, Antony, & Sykes, 2021 ; Tang, Hung, Au-Yeung, & Yuen, 2020 ; Tunc-Aksan & Akbay, 2019 ) and the rest had a high quality and low risk of bias judged by the authors.…”
Section: Resultsmentioning
confidence: 99%
“…The one-study-removed technique revealed that none of the included studies influenced or skewed the final results. However, among 85 articles (86 effect-sizes) included in the analysis, 21 articles had a moderate risk of bias (Alt & Boniel-Nissim, 2018a, 2018bBarber & Santuzzi, 2017;Barry & Wong, 2020;Burnell, George, Vollet, Ehrenreich, & Underwood, 2019;Buyukbayraktar, 2020;Classen, Wood, & Davies, 2020;Elhai et al, 2016;Fuster, Chamarro, & Oberst, 2017;Hishan, Ramakrishnan, & Qureshi, 2020;McAndrew, 2018;Metin-Orta, 2020;Munawaroh, Nurmalasari, & Sofyan, 2020;O'Connell, 2020;Rahardjo & Mulyani, 2020;Riordan et al, 2020…”
Section: Sensitivity Analysis Quality and Risk Of Bias Assessmentmentioning
confidence: 99%
“…According to Moore and Craciun (2020), individuals with higher fear of missing out are reported to have good attitudes on Instagram, become followers of more Instagram accounts, and have a stronger tendency towards social media addiction. In Munawaroh, Nurmalasari, and Sofyan (2020), it is stated that whenever individuals feel bored or uncomfortable, they will access Instagram. Furthermore, Rahardjo and Mulyani (2020) said that individuals with poor social competence tend to build relationships with the online form.…”
Section: Fomo and Its Relation To Type Duration Of Use Of Social Media And Ethnicitymentioning
confidence: 99%
“…Research by [30] states that the higher the user's dependence on Instagram, the stronger the perceived FoMO is characterized by, and the more intensively users search for the latest information related to other people's activities. Instagram's ease of access makes its users addicted FoMO has been widely applied for commercial purposes, but only some are interested in researching it for academic purposes [20].…”
Section: Introductionmentioning
confidence: 99%